2008
DOI: 10.3727/096368908787648056
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Endogenous Retrovirus (PERV) and its Transmission Characteristics: A Study of the New Zealand Designated Pathogen-Free Herd

Abstract: Previously a strategy for monitoring of pigs intended for cell transplantation was developed and successfully applied to several representative herds in New Zealand. A designated pathogen-free (DPF) herd has been chosen as a good candidate for xenotransplantation. This herd has previously tested free of infectious agents relevant to xenotransplantation and we present here an in depth study of porcine endogenous retrovirus (PERV) transmission. A panel of assays that describes the constraints for the transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
(6 reference statements)
2
32
0
Order By: Relevance
“…PERV-A/C were until now detected only in miniature pigs and in these animals only in certain organs, e.g., in the spleen, but not in other organs and never in the germ line ( , [Harrison et al, 2004] and [Dieckhoff et al, 2007]). PERV-A/C were also not found in the New Zealand designated pathogen-free herd (Garkavenko et al, 2008). However, there are new reports on PERV-A/C in commercially used pigs with an increased number in clinically affected animals (Pal et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…PERV-A/C were until now detected only in miniature pigs and in these animals only in certain organs, e.g., in the spleen, but not in other organs and never in the germ line ( , [Harrison et al, 2004] and [Dieckhoff et al, 2007]). PERV-A/C were also not found in the New Zealand designated pathogen-free herd (Garkavenko et al, 2008). However, there are new reports on PERV-A/C in commercially used pigs with an increased number in clinically affected animals (Pal et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…To ensure the release of infectious PERV particles (if any), tested cells were mitogenically stimulated prior to co-culture with standard susceptible cell lines 293 (to elucidate xeno-tropic PERV) and St-Iowa (to elucidate eco-tropic PERV). Although mitogenic stimulation enhanced proliferation of all tested cells, no evidence of PERV transmission was detected in the infectivity test with both human and pig target cells using PBMC or islet cells isolated from the New Zealand SPF pigs Garkavenko, Wynyard, Nathu, Simond, et al, 2008). Thus it was concluded that the New Zealand SPF pigs could be classified as non-transmitters for PERV, possessing the "null" transmission phenotype.…”
Section: Perv Infectivity In Vitro -The Gold Standardmentioning
confidence: 86%
“…Moreover, endogenous retroviruses behave like normal cellular genes in that they are inherited by the offspring and not acquired by infection. Accordingly PERV cannot be removed by conventional barrier methods instead requiring more elaborate strategies such as the selective breeding of pigs with favourable PERV genetic characteristics Garkavenko, Wynyard, Nathu, Simond, Muzina et al, 2008;Stoye et al, 1998), or the development of vaccines to protect against PERV transmission or the inhibition of PERV expression by RNA interference using PERV-specific short hairpin RNA (shRNA) and retroviral vectors [reviewed in (Denner, 2008)]. Like most retroviruses PERV has an element of unpredictability in regards to its transmission potential.…”
Section: Porcine Endogenous Retrovirus (Perv) -Developing a Standard mentioning
confidence: 99%
See 2 more Smart Citations